2022
DOI: 10.1177/1358863x221091320
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lipoprotein (a) levels and risk of peripheral artery disease outcomes: A systematic review

Abstract: Background: Despite strong association of elevated lipoprotein (a) (Lp(a)) levels with incident coronary and cerebrovascular disease, data for incident peripheral artery disease (PAD) are less robust. The main objective of the present systematic review was to analyze the association between elevated Lp(a) levels and PAD outcomes. Methods: This systematic review was performed according to PRISMA guidelines. A literature search was performed to detect randomized clinical trials or observational studies with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Elevated lipoprotein(a) is a well‐established risk factor for multiple cardiovascular diseases (CVDs), especially coronary artery disease and aortic stenosis (AS). 1 Lipoprotein(a) is also associated with ischemic stroke, 2 , 3 peripheral vascular disease (PVD), 4 and heart failure (HF). 5 The accumulation of epidemiologic and genetic studies strongly supports a causal role for lipoprotein(a) in CVD in diverse populations, even with low levels of low‐density lipoprotein cholesterol.…”
mentioning
confidence: 99%
“…Elevated lipoprotein(a) is a well‐established risk factor for multiple cardiovascular diseases (CVDs), especially coronary artery disease and aortic stenosis (AS). 1 Lipoprotein(a) is also associated with ischemic stroke, 2 , 3 peripheral vascular disease (PVD), 4 and heart failure (HF). 5 The accumulation of epidemiologic and genetic studies strongly supports a causal role for lipoprotein(a) in CVD in diverse populations, even with low levels of low‐density lipoprotein cholesterol.…”
mentioning
confidence: 99%
“…In a systematic review including 15 studies and 493,650 patients, most studies confirmed a significant association between high Lp(a) levels and the risk of PAD. High Lp(a) levels have also been found to be associated with increased PAD progression, risk of intermittent claudication, recurrence of significant stenosis and risk of hospitalisation and death [ 55 ]. Higher levels of Lp(a) have been shown to be independently associated with an increased risk of major adverse limb events (MALE) [ 56 ].…”
Section: Lipoprotein(a) and Cardiovascular Diseasementioning
confidence: 99%
“…A recent systematic review analyzed 15 studies involving 493,650 patients, and the majority of these studies supported a significant association between high Lp(a) levels and the risk of PAD, according to the authors. High Lp(a) levels were also found to be linked to an increased risk of claudication, PAD progression, restenosis, hospitalization, and death [ 121 ] ( Figure 2 ).…”
Section: Lp(a) In Vascular Diseasesmentioning
confidence: 99%